Dicyclo-hexyl-ammonium bis-(chloro-difluoro-acetato-κO)cyclo-pentyl-diphenyl-stannate(IV). - Teo, Y.Y.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2008)
The five-coordinate Sn atom in the title mixed organyl stannate compound, (C(12)H(24)N)[Sn(C(5)H(9))(C(6)H(5))(2)(C(2)ClF(2)O(2))], is in a trans-C(3)SnO(2) trigonal-bipyramidal coordination environment. The NH(2) groups of the cations act as hydrogen-bond donors to two symmetry-related anions, resulting in the formation of linear chains. One of the phenyl rings is disordered over two sites with equal occupancies.